2020
DOI: 10.1155/2020/3792728
|View full text |Cite
|
Sign up to set email alerts
|

Leucocytosis and Asymptomatic Urinary Tract Infections in Sickle Cell Patients at a Tertiary Hospital in Zambia

Abstract: Sickle cell anaemia (SCA) is an inherited disease resulting from mutations in the β-globin chain of adult haemoglobin that results in the formation of homozygous sickle haemoglobin. It is associated with several complications including an altered blood picture and damage in multiple organs, including the kidneys. Kidney disease is seen in most patients with SCA and may affect glomerular and/or tubular function, thereby putting these patients at risk of urinary tract infections. However, there is a paucity of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Monocytes play a vital role in scavenging dead cells and sickled red cells. The monocytosis among SCD patients in this study is probably part of the "patrolling monocytes" which protect against vascular damage by scavenging cellular debris and ameliorate VOC in SCD [34]. In this study, the increased population of monocytes, post-administration of the test drug, probably supports in repairing tissues that are already damaged as a result of reduced perfusion by stopping the inflammatory process and evacuating necrotic cells from the site of tissue damage and possibly cytokine production.…”
Section: Discussionmentioning
confidence: 59%
“…Monocytes play a vital role in scavenging dead cells and sickled red cells. The monocytosis among SCD patients in this study is probably part of the "patrolling monocytes" which protect against vascular damage by scavenging cellular debris and ameliorate VOC in SCD [34]. In this study, the increased population of monocytes, post-administration of the test drug, probably supports in repairing tissues that are already damaged as a result of reduced perfusion by stopping the inflammatory process and evacuating necrotic cells from the site of tissue damage and possibly cytokine production.…”
Section: Discussionmentioning
confidence: 59%
“…This finding is inconsistence with Seifu and Gebissa [34] in Ethiopia who reported E. coli as the commonly uropathogens from UTI patients. In other reports, Many et al [39] in DRC, reported P. mirabilis (41.2%), Labi et al [24] in Ghana, reported Enterococcus sp (26.7%) and Musonda et al [40] in Zambia, reported Staphylococcus aureus (32%) as the most predominant organism. The variation in the type of bacteria uropathogens in this study and others reported might be attributed to physiological state of patients, techniques of sample collection, sample size used, environmental or personal hygiene.…”
Section: Discussionmentioning
confidence: 85%
“…[24] in Ghana, reported Enterococcus sp (26.7%) and Musonda et al . [40] in Zambia, reported Staphylococcus aureus (32%) as the most predominant organism. The variation in the type of bacteria uropathogens in this study and others reported might be attributed to physiological state of patients, techniques of sample collection, sample size used, environmental or personal hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…In other reports, Many et al, (39) in Democratic Republic of Congo (DRC) reported P. mirabilis (41.2%), Labi et al, (24) in Ghana reported Enterococcus sp. (26.7%) and Musonda et al, (40) in Zambia reported S. aureus (32%) as the most predominant organism. The variation in the type of bacteria uropathogens in this study and others reported might be attributed to physiological state of patients, techniques of sample collection, sample size used, environmental or personal hygi ene levels.…”
Section: Discussionmentioning
confidence: 85%